Regulatory Mechanisms of Autophagy-Targeted Antimicrobial Therapeutics Against Mycobacterial Infection - Silwal, Prashanta; Paik, Seungwha; Kim, Jin Kyung; Yoshimori, Tamotsu; Jo, Eun-Kyeong (Frontiers in Cellular and Infection Microbiology, 2021)
Several autophagy-modulating agents show promise as host-directed therapeutics for Mycobacterium tuberculosis (Mtb) infection. Although the underlying molecular mechanisms by which autophagy-activating agents enhance antimicrobial responses against Mtb are unclear, modulation of innate immunity, inflammation, phago-lysosomal function, and metabolic pathways are postulated to be involved. Here, we discuss the mechanisms of action of autophagy-modulating agents with overcoming the immune escape strategies induced by Mtb pathogens. The factors and pathways that govern such mechanisms include adenosine 5′-monophosphate-activated protein kinase, Akt/mammalian TOR kinase, Wnt signaling, transcription factor EB, cathelicidins, inflammation, endoplasmic reticulum stress, and autophagy-related genes. An understanding of these mechanisms will facilitate the development of host-directed therapies against tuberculosis as well as other emerging and re-emerging infections.